Urdu translation and validation of clinically useful depression outcome scale - Yasmeen Wajid Mauna Gauhar; Humaira Jami (Journal of the Pakistan Medical Association, 2021)
Objective: To translate and validate Clinically Useful Depression Outcome Scale on Urdu speaking Pakistani population. Method: This cross-sectional study was conducted in Rawalpindi and Islamabad from January 2018 to November 2019 on a conveniently available sample. The process of translation and validation was conducted in two phases. In the first phase the scale was forward and backward translated. In the second phase it was validated on a convenient sample of 170 subjects. 85 of these were from clinical and 85 were from non-clinical setting. After descriptive analysis, Cronbach’s alpha as a reliability coefficient, test-retest reliability, item-to-total correlation for internal consistency, Pearson product-moment for convergent and discriminant validity, and independent sample t-test for contrast group mean comparison were computed for validation purpose on the data through SPSS 22. Cross-language validation and mean comparison of the original and translated scale were established on a separate sample of 82 participants as indicators for equivalence. Result: The translated scale was found to be internally consistent with satisfactory Cronbach’s alpha and test-retest reliabilities. Convergent and discriminant validity were in assumed directions. Significant mean differences between clinical and non-clinical groups indicated the diagnostic capability of the scale. Significant cross-language correlations and non-significant mean differences between original and translated version showed that the Urdu version can be considered as equivalent to original English version. Conclusion: Results of the study found the translated scale to be as a reliable and valid Instrument. Keywords: Depression, Urdu-translation, psychometrics, reliability, validity. Continuous....